1985
DOI: 10.1159/000249434
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Cicatricial Pemphigoid

Abstract: A patient is presented with generalized blistering and scarring eruptions, showing immunopathological, histological and electron microscopical characteristics of disseminated cicatricial pemphigoid, successfully treated by combined therapy of systemic steroids and azathioprine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[112][113][114][115][116][117][118][119][120][121][122][123][124][125] Although one prospective study showed no significant benefit with the addition of azathioprine as an adjuvant to prednisolone, 116 the possibility of underdosing has been suggested. 126 Some clinicians believe that azathioprine is effective in the treatment of pemphigoid and prefer it over other immunosuppressant medications.…”
Section: Immunobullous Diseasesmentioning
confidence: 99%
“…[112][113][114][115][116][117][118][119][120][121][122][123][124][125] Although one prospective study showed no significant benefit with the addition of azathioprine as an adjuvant to prednisolone, 116 the possibility of underdosing has been suggested. 126 Some clinicians believe that azathioprine is effective in the treatment of pemphigoid and prefer it over other immunosuppressant medications.…”
Section: Immunobullous Diseasesmentioning
confidence: 99%